Pembaruan Hukum Pidana dalam Perspektif Perlindungan Korban: Studi Kritis Terhadap Penguatan Hak Korban dalam Undang-Undang No. 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana - Eka Putra Zakran; Budi Sastra Panjaitan; Arifuddin Muda Harahap (Pusat Riset dan Inovasi Nasional, 2025)
The reform of criminal law in Indonesia through Law No. 1 of 2023 concerning the Criminal Code (KUHP) marks an important paradigm shift in the criminal justice system, especially related to the protection of victims of crimes. So far, the orientation of the Criminal Code of colonial heritage has emphasized more on the perpetrators of crimes, while victims are often positioned passively and marginalized. This article aims to critically examine the extent to which Law No. 1 of 2023 strengthens the rights of victims, both in material and procedural aspects. With a normative juridical approach and an analysis of the new norms in the National Criminal Code, this article finds that a number of provisions, such as the victim's right to restitution, participation in judicial proceedings, and identity protection, reflect a greater recognition of the interests of the victim. However, in practice, there are still implementation challenges, including limitations in the mechanism for the implementation of these rights, as well as potential inequalities in access to justice. Therefore, it is necessary to strengthen derivative regulations, socialization, and synergy between law enforcement agencies to ensure that victim protection runs effectively and fairly.